2016
DOI: 10.1080/00016357.2016.1191086
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence among adolescents in Bergen, Western Norway, of temporomandibular disorders according to the DC/TMD criteria and examination protocol

Abstract: Objective. The aims of this study were to assess the prevalence of temporomandibular disorders (TMD) amongst adolescents and to contrast the prevalence of TMD according to the DC/TMD clinical examination protocol versus the prevalence of TMD pain according to two screening questions. Material and methods. Two hundred and ten adolescents living in the county of Bergen, Norway, were offered an additional examination for TMD in connection with their regular dental check-up appointment. Five dental clinics were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
54
4
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 20 publications
12
54
4
4
Order By: Relevance
“…This is similar to the results done in the previous studies by Graue et al .,[10] Solberg et al .,[14] Klineberg et al .,[15] Shiau and Chang. [16] This high prevalence among females could be due to the physiologic uniqueness such as regular hormonal variations, different characteristics of the connective tissue, and muscular structure.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is similar to the results done in the previous studies by Graue et al .,[10] Solberg et al .,[14] Klineberg et al .,[15] Shiau and Chang. [16] This high prevalence among females could be due to the physiologic uniqueness such as regular hormonal variations, different characteristics of the connective tissue, and muscular structure.…”
Section: Discussionsupporting
confidence: 92%
“…[789] Graue et al . [10] stated that girls were more prone for developing TMDs usually peaking at 16 years age.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of TMD-P in Rogaland County was 7%. Another Norwegian study ( n = 167) found a prevalence of 7.2% among adolescents in the city of Bergen based on the TMD-P questions, but the DC/TMD criteria for TMD indicated a prevalence of 11.9% [13]. The findings of the present study are in accordance with a Swedish study from 1999 that included 862 adolescents (12 to 18 years old), with a prevalence of TMD-P of 7% [11].…”
Section: Discussionsupporting
confidence: 88%
“…Several other studies have found similar ratios, ranging from 2 : 1 up to 9 : 1 [10–13, 19, 20, 26, 27]. This study did not find such differences at ages 13 and 14, while other studies did not find differences before puberty [7, 28].…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation